2020
DOI: 10.1021/acs.joc.9b02767
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of All Six Chiral Natural Pyrethrins: Accurate Determination of the Physical Properties, Their Insecticidal Activities, and Evaluation of Synthetic Methods

Abstract: Chiral total syntheses of all six insecticidal natural pyrethrins (three pyrethrin I and three pyrethrin II compounds) contained in the chrysanthemum (pyrethrum) flower were performed. Three common alcohol components [(S)-cinerolone, (S)-jasmololone, and (S)-pyrethrolone] were synthesized: (i) straightforward Sonogashira-type cross-couplings using available (S)-4-hydroxy-3-methyl-2-(2-propynyl)­cyclopent-2-en-1-ones (the prallethrin alcohol) for (S)-cinerolone (overall 52% yield, 98% ee) and (S)-pyrethrolone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 62 publications
(66 reference statements)
0
36
0
Order By: Relevance
“…The previous work of our group showed that pyrethrin II and pyrethrin I exhibited similar potencies on cockroach sodium channels expressed in the Xenopus oocytes 23 . A very recent study reported that the order of potency of both knockdown and killing for the six pyrethrins against Culex pipiens pallens , ranging from high to low, was pyrethrin I > cinerin I > cinerin II > pyrethrin II > > jasmolin I > jasmolin II 39 . The discrepancies in the repellency versus insecticidal activity for each pyrethrin are interesting and likely reflect differential binding affinities of each pyrethrin to olfactory receptors versus sodium channels.…”
Section: Discussionmentioning
confidence: 81%
“…The previous work of our group showed that pyrethrin II and pyrethrin I exhibited similar potencies on cockroach sodium channels expressed in the Xenopus oocytes 23 . A very recent study reported that the order of potency of both knockdown and killing for the six pyrethrins against Culex pipiens pallens , ranging from high to low, was pyrethrin I > cinerin I > cinerin II > pyrethrin II > > jasmolin I > jasmolin II 39 . The discrepancies in the repellency versus insecticidal activity for each pyrethrin are interesting and likely reflect differential binding affinities of each pyrethrin to olfactory receptors versus sodium channels.…”
Section: Discussionmentioning
confidence: 81%
“…Production of the final carbon scaffold could be readily achieved by implementing similar Sonogashira cross-coupling conditions to those used by Matsuo and co-workers. 5,7 Prior to addition of the catalytic components, a solution of vinyl bromide in THF was deaereated with argon to prevent the competitive Glaser coupling of the alkynyl substrate 7. The enyne 8 was generated by reaction with the vinyl bromide in the presence of Pd(Ph3P)4, CuI and Et3N.…”
Section: Author(s)mentioning
confidence: 99%
“…More recently, a shorter reaction time and alternate solvent mixture have been described. 5 Notably, these reactions require the use of over 150 equivalents of activated zinc which may contribute to the observed over-reduction and generate significant quantities of heavy metal waste. Optimisation of this protocol allowed for a significant drop in the amount of zinc used from the aforementioned 150 to 20 equivalents.…”
Section: Author(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our continuing interest in chiral discrimination studies between enantiomers and diastereomers [ 18 , 19 , 20 , 21 , 22 , 23 ], a major topic in pharmaceutical and agrochemical research, we envisaged the chiral total syntheses of three sets of plymuthipyranones to evaluate the anti -MRSA activity of natural plymuthipyranone B (more active than A), synthetic analogues 4c , 4d and novel synthetic analogue 4e . This study is closely related to our total synthetic studies of a 3-acyl-5,6-dihydro-2 H -pyran-2-one series [ 7 , 10 , 15 ] and relevant 4-methoxy derivatives (all four stereoisomers of pestalotin) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%